Implementing the Concept of Co-Parenting in Divorce Cases: An Analysis Using the Maslahah Approach - Turnip, Ibnu Radwan Siddik; Harahap, Sumper Mulia; Talli, Abdul Halim; Arminsyah, Arminsyah; Sebyar, Muhamad Hasan (AL-ISTINBATH : Jurnal Hukum Islam, 2024)
This study aims to analyze the application of child rights protection in divorce decisions at the Cirebon Religious Court and explore ways to optimize this protection using the maslahah approach. Divorce significantly impacts the physical and mental development of children, often resulting in a weakened next generation due to the lack of fulfillment of children's rights post-divorce. The research employs a normative juridical method, incorporating statute, case, and conceptual analyses to provide a comprehensive understanding of the current legal landscape and its shortcomings. The findings reveal that while the inclusion of children's rights in divorce decisions is crucial, it remains optional rather than mandatory. This oversight leaves many children vulnerable, as their rights are not consistently safeguarded in the aftermath of their parents' separation. Currently, no regulation mandates the inclusion of children's rights in divorce decrees, limiting judges to act only on explicit petitions. This study highlights the effectiveness of the Maslahah approach in ensuring that children's rights are prioritized, recommending significant legal reforms to make the inclusion of these rights mandatory in divorce rulings. Such reforms would provide a robust legal foundation to safeguard children's human rights post-divorce, covering aspects such as education, health, and protection from parental conflict. By implementing these recommendations, we can enhance the well-being of children affected by divorce and ensure their rights are consistently protected.